Dynamic Changes of Functional Pain Connectome in Women with Primary Dysmenorrhea - Wu, Ting-Hsuan (Sci Rep, 2016)
Primary dysmenorrhea (PDM) is the most prevalent gynecological problem. Many key brain systems are engaged in pain processing. In light of dynamic communication within and between systems (or networks) in shaping pain experience and behavior, the intra-regional functional connectivity (FC) in the hub regions of the systems may be altered and the functional interactions in terms of inter-regional FCs among the networks may be reorganized to cope with the repeated stress of menstrual pain in PDM. Forty-six otherwise healthy PDM subjects and 49 age-matched, healthy female control subjects were enrolled. Intra- and inter-regional FC were assessed using regional homogeneity (ReHo) and ReHo-seeded FC analyses, respectively. PDM women exhibited a trait-related ReHo reduction in the ventromedial prefrontal cortex, part of the default mode network (DMN), during the periovulatory phase. The trait-related hypoconnectivity of DMN-salience network and hyperconnectivity of DMN-executive control network across the menstrual cycle featured a dynamic transition from affective processing of pain salience to cognitive modulation. The altered DMN-sensorimotor network may be an ongoing representation of cumulative menstrual pain. The findings indicate that women with long-term PDM may develop adaptive neuroplasticity and functional reorganization with a network shift from affective processing of salience to the cognitive modulation of pain.